2020
DOI: 10.3389/fcimb.2020.610121
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator or Brake: Immune Regulators in Malaria

Abstract: Malaria is a life-threatening infectious disease, affecting over 250 million individuals worldwide each year, eradicating malaria has been one of the greatest challenges to public health for a century. Growing resistance to anti-parasitic therapies and lack of effective vaccines are major contributing factors in controlling this disease. However, the incomplete understanding of parasite interactions with host anti-malaria immunity hinders vaccine development efforts to date. Recent studies have been unveiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 307 publications
0
5
0
Order By: Relevance
“…In malaria infection, natural regulatory T cells and positive/negative regulators have been shown to play a role in balancing immune responses to maintain vertebrate defense and immune balance. Plasmodium exploits regulatory mechanisms to prevent the development of adaptive immunity by enhancing negative regulators and/or inhibiting positive regulators including reduced T-cell proliferative responses to Plasmodium antigens and production of immunosuppressive IL-10 [ 62 ]. Negative regulators such as BTLA have been reported to dampen innate and T-/B-cell-mediated immune response to malaria infection [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In malaria infection, natural regulatory T cells and positive/negative regulators have been shown to play a role in balancing immune responses to maintain vertebrate defense and immune balance. Plasmodium exploits regulatory mechanisms to prevent the development of adaptive immunity by enhancing negative regulators and/or inhibiting positive regulators including reduced T-cell proliferative responses to Plasmodium antigens and production of immunosuppressive IL-10 [ 62 ]. Negative regulators such as BTLA have been reported to dampen innate and T-/B-cell-mediated immune response to malaria infection [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of IFNs signaling drive the activation and maturation of antigen-presenting cells such as macrophages and dendritic cells (DCs), which subsequently present the antigens to naive T cell through a combination of major histocompatibility complex (MHC) and T cell receptor (TCR), thereby engaging the differentiation of naive T or B lymphocytes to initiate cellular and humoral immunity for eventual virus clearance. 312 , 313 A few studies have identified that RNF proteins regulate several steps in adaptive immune responses against viral infection (Fig. 6 ).…”
Section: Rnf Family Proteins In Viral Infectionmentioning
confidence: 99%
“…Malaria is still the most important life-threatening parasitic disease according to the World Health Organisation report, with an estimated 229 million cases and 409,000 deaths occurring in 2019. The immune response during malaria is complex, and immune depression has been described as an important malaria complication [ 1 , 2 , 3 , 4 , 5 ]. Mechanisms and pathomechanistic factors involved in imbalanced immune response are partly known, but many players still need to be investigated.…”
Section: Introductionmentioning
confidence: 99%